Zinc Oxide Nanoparticles Protected with Terpenoids as a Substance in Redox Imbalance Normalization in Burns - Nina Melnikova; Alyona Balakireva; Dmitry Orekhov; Denis Kamorin; Natalia Didenko; Darina Malygina; Alexander Knyazev; Denis Novopoltsev; Anna Solovyeva (MDPI AG, 2021)
Preliminary protection of zinc oxide nanoparticles (ZnO NPs) with terpenoids such as betulin, its derivatives, and essential oils components has been proposed to produce gel-like oleophilic and hydrophilic formulations. We studied the properties of gel-like dispersions of ZnO NPs with immobilized terpenoids and their effects on the activity of LDH, GR, G6PDH, restoration of redox balance of co-enzyme pairs NAD+/NADH and NADP+/NADPH, as well as the activity of SOD, catalase, AlDH in erythrocytes in the treatment of burns in rats. Hysteresis loops on the rheograms of studied dispersions characterize their thixotropic properties. ZnO NPs with betulin diphosphate in the water-ethanol medium lead to a 20-fold increase in the hydrodynamic radius at pH 7.3 compared to the initial ZnO NPs, and facilitate the formation of Zn2+ ions and their penetration into the viable epidermis, unlike oleophilic dispersions. All dispersions reduce the healing time by one and a half times compared with the untreated control group, increase the activity of LDH, GR, G6PDH, SOD, catalase, AlDH, and contribute to the normalization of coenzyme balance. Normalization of the redox balance and wound state was more effective using hydrophilic dispersions due to Zn2 + penetration.